Microorganism knowledge and hygiene behavior among senior high school students - M. Rafi Dhiaulhaq; Ali Mustofa (Universitas Negeri Jakarta, 2026)
Public understanding of microorganisms is a critical component of scientific literacy, particularly in the context of infectious disease prevention. However, research consistently documents persistent misconceptions and fragmented knowledge among secondary school students, underscoring the need for evidence-based evaluation of microbiology literacy in formal education settings. This study aimed to evaluate the levels of knowledge, attitudes, perceptions, and behaviors of senior high school students regarding microorganism-related issues within a biology education context. A cross-sectional survey design was employed involving 188 eleventh- and twelfth-grade students from senior high schools in Tuban Regency, East Java, Indonesia. Data were collected using a structured questionnaire encompassing four dimensions: knowledge (6 Likert-scale items), attitudes (6 Likert-scale items), perceptions (7 multiple-choice items), and behaviors (7 multiple-choice items), and were analyzed descriptively. Results revealed that students' knowledge was categorized as high (mean = 3.15). However, conceptual understanding remained fragmented, with students predominantly perceiving microorganisms as harmful agents. Perceptions fell within the moderate category, reflecting a gap between factual knowledge and integrated scientific understanding. Attitudes were very high overall (mean = 3.48), though inconsistencies were evident in food safety decision-making. Hygiene-related behaviors were generally high; however, discrepancies were observed in food storage practices and disinfectant use. These findings indicate that strong basic knowledge and positive attitudes do not automatically translate into consistent and appropriate health behaviors. Biology education programs must therefore adopt integrative instructional approaches that explicitly connect microbiological concepts with real-world applications to bridge knowledge-attitude-behavior gaps and promote health-literate graduates.